Tagar, Wacana, dan Perlawanan: Studi Tentang #KawalPutusanMK Sebagai Simbol Mobilisasi Gerakan Sosial - Luntungan, Rodrigo Mauris (Jurnal Ilmiah Widya Sosiopolitika; Vol 6 No 2 (2024): ISU-ISU PEMBANGUNANDO - 10.24843/JIWSP.2024.v06.i02.p03, 2025)
Recently, social media has been buzzing about a movement aimed at preserving the decisions of The Constitutional Court (MK – Mahkamah Konstitusi ). The hashtag #KawalPutusanMK is used as a tool for mobilizing social movements in Indonesia, particularly related to the protest actions on August 21, 2024. Amid the increasing use of social media as a means to express opinions, this study examines how the hashtag functions as a symbol that motivates people to express their dissatisfaction with The Constitutional Court's decisions regarding the regional elections (Pilkada – Pemilihan Kepala Daerah ) law. Using a qualitative approach and discourse analysis, this research collects data from social media platforms such as Instagram, X, and TikTok to identify the factors that triggered the emergence of the hashtag and its impact on mass mobilization. The findings indicate that # KawalPutusanMK encourages the dissemination of information and the building public support, thereby creating an interactive network that enhances public awareness of social issues. This hashtag not only serves as a tool for organizing protest actions but also legitimizes the demands for social change put forth by the community, reflecting new dynamics in social movements in the digital era. As a direct outcome of this movement, the hashtag contributed to the cancellation of the draft regional elections law ( RUU Pilkada ), demonstrating how public mobilization using the hashtag #KawalPutusanMK can influence political decisions and result in concrete policy changes.